Experimental Investigation into the Number of Phases in Debris Flows - Bin Li; Ze-Min Xu (Applied Sciences)
Controversial number of phases in debris-flow masses involves almost all areas of debris-flow research. In this study, we experimentally investigated the number of phases in fully developed debris flows using six sediments with three maximum diameters of up to 30 mm from two representative debris-flow deposits in China. Fluid escape tests, displacement experiments, relative motion experiments, and rheometrical tests were conducted using 12 slurries prepared with the sediments. The results from four types of experiments show that debris flows are close to one-phase flow and far from two-phase flow. Under both gravity and artificial hydraulic and mechanical forcing, no relative motion of water or fluid composed of water and fine-grained particles and solids occurs in both the experimental flows and static slurries. This suggests that the water and solids in debris flows move together as a single fluid, and are deposited by “freezing”. The rheological behavior of the experimental debris flows is similar to that of Bingham materials. This indicates that debris flows may be approximated as continuous, homogeneous, isotropic fluids. In conclusion, debris flows behave more like monophasic flow, are far from biphasic flow, and should be treated as one- rather than as two-phase flow.